ADAR1 Is Required for Dendritic Cell Subset Homeostasis and Alveolar Macrophage Function - Baal, Nelli; Cunningham, Sarah; Obermann, Hannah-Lena; Thomas, Jenny; Lippitsch, Anne; Dietert, Kristina; Gruber, Achim D.; Kaufmann, Andreas; Michel, Gabriela; Nist, Andrea; Stiewe, Thorsten; Rupp, Oliver; et al. (Journal of Immunology, 2019)
RNA editing by adenosine deaminases acting on dsRNA (ADAR) has become of increasing medical relevance, particularly because aberrant ADAR1 activity has been associated with autoimmunity and malignancies. However, the role of ADAR1 in dendritic cells (DC), representing critical professional APCs, is unknown. We have established conditional murine CD11c Cre-mediated ADAR1 gene ablation, which did not induce general apoptosis in CD11c(+) cells but instead manifests in cell type-specific effects in DC subpopulations. Bone marrow-derived DC subset analysis revealed an incapacity to differentiate CD103 DC+ in both bulk bone marrow and purified pre-DC lineage progenitor assays. ADAR1 deficiency further resulted in a preferential systemic loss of CD8(+)/CD103(+) DCs, revealing critical dependency on ADAR1, whereas other DC subpopulations were moderately affected or unaffected. Additionally, alveolar macrophages were depleted and dysfunctional, resembling pulmonary alveolar proteinosis. These results reveal an unrecognized role of ADAR1 in DC subset homeostasis and unveils the cell type-specific effects of RNA editing.
CRIS-Team WoS Importer:2019-02-21

Biomimetic Magnetic Particles for the Removal of Gram-Positive Bacteria and Lipoteichoic Acid. - Friedrich, Bernhard; Eichermüller, Julia; Bogdan, Christian; Cunningham, Sarah; Hackstein, Holger; Strauss, Richard; Alexiou, Christoph; Lyer, Stefan; Tietze, Rainer (Pharmaceutics, 2022)
Gram+ bacteria are very common in clinical medicine and responsible for a large number of infectious diseases. For example, Gram+ bacteria play a major role in causing bloodstream infections and sepsis. Therefore, the detection of Gram+ bacteria is of great importance for the diagnosis and treatment of infectious diseases. Furthermore, these bacteria are often present in biofilms that cover implants. Recent research work has mainly focused on the biologic activity and removal of Gram-negative bacteria or bacterial components such as lipopolysaccharides (LPS). In contrast, the effects of lipoteichoic acid (LTA) have been less well studied so the relevance of their removal from body fluids is possibly underestimated. To address this topic, we evaluated superparamagnetic iron oxide particles (SPION) carrying different peptides derived from the innate immune receptor (GP-340) for their ability to bind and remove Gram+ bacteria and LTA from different media. Our results show that, beyond S. aureus, effective agglutinating and removing of S. pneumoniae was possible. Furthermore, we were able to show for the first time that this was possible with LTA alone and that the magnetic removal of bacteria was also efficient under flow conditions. We also found that this method was able to capture Stapyhylococcus aureus from platelet concentrates, which can help to enhance the sensitivity of microbiological diagnostics, quality control measures, and blood product safety.
EVALuna2:508460

Characterization of the impact of immune checkpoint inhibitors on platelet activation and aggregation - Schlüter, Julian; Cunningham, Sarah; Zimmermann, Robert; Achenbach, Susanne; Kramer, Rafaela; Erdmann, Michael; Beckmann, Matthias; Heinzerling, Lucie; Hackstein, Holger (Immunobiology, 2023)
Immune checkpoint inhibitors (ICIs) are effective oncological drugs which block cellular check-point receptors typically targeted by tumor immune evasion strategies. Despite their benefits, clinicians have reported treatment-associated thromboembolism during ICI therapy in recent years. Though several theories on this ICI-associated pathogenesis exist, the direct effects of ICIs on platelets remains unknown. We therefore investigated the potential direct and indirect effect of PD-1, PD-L1 and CTLA-4-targeting ICIs on platelet functionality in multifaceted in vitro experiments. Interestingly, we could not observe a clear effect of ICI on platelet aggregation and primary hemostasis in whole blood and platelet concentrate-based assays. Furthermore, the presence of ICIs in toll-like receptor stimulation had no significant impact on platelet surface marker expression. In a second approach, we investigated the indirect immunological impact of ICIs on platelet activation by exposing platelets to supernatants from ICI- and Staphylococcal enterotoxin B-exposed PBMCs. Whereas ICIs affected IL-2 levels in supernatants, we could not detect clear differences in the secretion of pro-thrombogenic factors and platelet responses. The obtained data suggest that the direct influence of ICIs on platelet activation or the influence of altered T cell function on platelet activation cannot be considered a major factor in the development of thrombotic events.
CRIS-Team Scopus Importer:2023-01-13
Keywords: Immune checkpoint inhibitors; Platelet activation; Platelet function tests; Platelets; Thrombosis

Cord-blood-derived professional antigen-presenting cells: Functions and applications in current and prospective cell therapies - Cunningham, Sarah; Hackstein, Holger (International Journal of Molecular Sciences, 2021)
Human umbilical cord blood (UCB) represents a valuable source of hematopoietic stem cells, particularly for patients lacking a matching donor. UCB provides practical advantages, including a lower risk of graft-versus-host-disease and permissive human leukocyte antigen mismatching. These advantageous properties have so far been applied for stem cell, mesenchymal stromal cell, and chimeric antigen receptor T cell therapies. However, UCB-derived professional antigen-presenting cells are increasingly being utilized in the context of immune tolerance and regenerative therapy. Here, we review the cell-specific characteristics as well as recent advancements in UCB-based cell therapies focusing on dendritic cells, monocytes, B lymphocytes, innate lymphoid cells, and macrophages.
CRIS-Team Scopus Importer:2021-06-11
Keywords: Antigen presentation; Cell therapy; Immune reconstitution; Umbilical cord blood

Functional Heterogeneity of Umbilical Cord Blood Monocyte-Derived Dendritic Cells - Schweiger, Petra; Hamann, Livia; Strobel, Julian; Weisbach, Volker; Wandersee, Alexandra; Christ, Julia; Kehl, Sven; Weidenthaler, Filip; Antoniadis, Sophia; Hackstein, Holger; Cunningham, Sarah (Journal of Immunology, 2024)
Human umbilical cord blood (UCB) represents a unique resource for hematopoietic stem cell transplantation for children and patients lacking suitable donors. UCB harbors a diverse set of leukocytes such as professional APCs, including monocytes, that could act as a novel source for cellular therapies. However, the immunological properties of UCB monocytes and monocyte-derived dendritic cells (MoDCs) are not fully characterized. In this study, we characterized the phenotype and functions of UCB-MoDCs to gauge their potential for future applications. UCB exhibited higher frequencies of platelets and lymphocytes as well as lower frequencies of neutrophils in comparison with adult whole blood. Leukocyte subset evaluation revealed significantly lower frequencies of granulocytes, NK cells, and CD14+CD16− monocytes. Surface marker evaluation revealed significantly lower rates of costimulatory molecules CD80 and CD83 while chemokine receptors CCR7 and CXCR4, as well as markers for Ag presentation, were similarly expressed. UCB-MoDCs were sensitive to TLR1–9 stimulation and presented quantitative differences in the release of proinflammatory cytokines. UCB-MoDCs presented functional CCR7-, CXCR4-, and CCR5-associated migratory behavior as well as adequate receptor- and micropinocytosis-mediated Ag uptake. When cocultured with allogeneic T lymphocytes, UCB-MoDCs induced weak CD4+ T lymphocyte proliferation, CD71 expression, and release of IFN-γ and IL-2. Taken together, UCB-MoDCs present potentially advantageous properties for future medical applications.<br

Influence of the Immune Checkpoint Inhibitors on the Hemostatic Potential of Blood Plasma - Patalakh, Iryna; Wandersee, Alexandra; Schlüter, Julian; Erdmann, Michael; Hackstein, Holger; Cunningham, Sarah (Transfusion Medicine and Hemotherapy, 2024)
Introduction: Immune checkpoint inhibitors (ICIs) have revolutionized classical treatment approaches of various cancer entities, but are also associated with a number of side effects. One of these may be life-threatening clotting disorders with the risk of thrombotic or hemorrhagic complications, the mechanisms of which are still poorly understood. In the present study, we analyzed the direct effects of pembrolizumab, nivolumab, and ipilimumab on platelet aggregation as well as plasma coagulation followed by fibrinolysis in an ex vivo model. Methods: Microplate spectrometry was used to analyze aggregation, coagulation, and fibrinolysis in platelet-free (PFP) and platelet-rich (PRP) healthy donor plasma samples treated with pembrolizumab, nivolumab, ipilimumab, and appropriate isotype controls. Aggregation was induced by TRAP-6. Clotting of PFP and PRP followed by lysis was initiated with a tissue factor in a mixture of phosphatidylserine:phosphatidylcholine and the addition of t-PA. Among other parameters, the area under the curve (AUC) was used to compare the effect of ICIs on aggregation, coagulation, and fibrinolysis. Results: Upon direct contact with platelets, pembrolizumab stimulated platelet aggregation in PRP, while nivolumab and ipilimumab promoted disaggregation with corresponding changes in the AUC. Pembrolizumab and nivolumab, both PD-1 receptor inhibitors, had no effect on the plasma coagulation cascade. Ipilimumab, a CTLA-4 receptor inhibitor, significantly increased the rate of PRP clotting. When clotting was followed by lysis, all ICIs were found to prolong the growth of the PRP-derived fibrin clot and delay its elimination. This was manifested by an increase in AUC relative to control PRP. Conclusion: This study characterizes the potential impact of pembrolizumab, nivolumab, and ipilimumab on hemostasis. Nivolumab and ipilimumab are able to reduce aggregation and increase the procoagulant properties of platelets, which can cause side effects associated with hemostatic imbalance leading to thrombosis or bleeding. The observed ICI-specific effects may contribute to our understanding of the mechanisms by which ICI affects platelets and suggest how, in a clinical setting, to reduce coagulation disorders during ICI treatment in the future
Keywords: Immune checkpoint inhibitors; Aggregation; Coagulation; Fibrinolysis; Platelet-rich plasma; Platelets; Thrombocytes

Interdependence of coagulation with immunotherapy and BRAF/MEK inhibitor therapy: results from a prospective study - Beckmann, Malte; Schlüter, Julian; Erdmann, Michael; Kramer, Rafaela; Cunningham, Sarah; Hackstein, Holger; Zimmermann, Robert; Heinzerling, Lucie (Cancer Immunology, Immunotherapy, 2024)
Immune checkpoint inhibitor (ICI) therapies effectively treat a broadening spectrum of cancer entities but induce various immune-related side effects (irAEs). Recent reports suggest a correlation between ICI-induced systemic inflammation and thromboembolic events as well as an increased effectiveness by coadministration of anticoagulants. With cancer patients having a higher risk of thrombotic events per se, it is crucial to dissect and characterize the mechanisms that cause pro-coagulative effects induced by systemic tumor therapies and their potential interplay with anti-tumor response. A total of 31 patients with advanced skin cancer treated with either ICIs (n = 24) or BRAF/MEK inhibitors (n = 7) were longitudinally assessed for blood and coagulation parameters before as well as 7, 20 and 40 days after initiation of systemic tumor therapy. Changes were analyzed and compared between both groups. In addition, the influence of coagulation parameters on progression-free, recurrence-free and overall survival was investigated. The ICI cohort presented significantly increased factor VIII activity after one week of therapy (p 0.0225); while, protein S activity was reduced during the whole observation period. Additionally, von Willebrand factor activity and tissue factor concentrations increased under immunotherapy. Similar changes occurred under BRAF/MEK inhibitor therapy (BRAF/MEKi). Increased baseline levels of von Willebrand factor antigen and factor VIII:C before the start of ICI therapy correlated with a significantly higher risk of recurrence for patients receiving adjuvant immunotherapy. The findings suggest the induction of a pro-coagulant state under ICI and BRAF/MEKi and a role of coagulation parameters in the efficacy of ICI therapie
Keywords: Immune checkpoint inhibitors; BRAF/MEK inhibitors; Melanoma; Coagulation–fibrinolysis disorders; ICI-associated thrombosis; Predictive marker

Medium supplementation with human, but not fetal calf serum facilitates endocytosis of PLGA nanoparticles by human primary B-lymphocytes via complement opsonization - Pusch, Lennart; Brox, Regine; Cunningham, Sarah; Fischer, Dagmar; Hackstein, Holger (Biochemical and Biophysical Research Communications, 2023)
The “biological identity” of nanoparticles (NPs) is governed by a shell consisting of various biomolecules that is formed upon exposure to biological media, the so-called biomolecule corona. Consequently, supplementation of cell culture media with e.g. different sera is likely to affect interactions between cells and NPs ex-vivo, especially endocytosis. We aimed to investigate the differential impact of human and fetal-bovine serum on the endocytosis of poly (lactic-co-glycolic acid) NPs by human peripheral blood mononuclear cells via flow cytometry. Furthermore, we employed different methods to inhibit endocytosis, providing mechanistic insights. The resulting biomolecule corona was characterized via denaturing gel electrophoresis. We found profound differences between human and fetal bovine serum regarding the endocytosis of fluorescently labeled PLGA nanoparticles by different classes of human leukocytes. Uptake by B-lymphocytes was particularly sensitive. We further present evidence, that these effects are mediated by a biomolecule corona. We demonstrate to our knowledge for the first time that the complement is an important contributor to the endocytosis of non-surface-engineered PLGA-nanoparticles prepared via emulsion solvent evaporation by human immune cells. Our data demonstrates that results obtained with xenogeneic culture supplements such as fetal bovine serum may have to be interpreted with caution.
CRIS-Team Scopus Importer:2023-03-24
Keywords: Biomolecule corona; Complement; Culture medium; Nanoparticles; PLGA

Plasmacytoid dendritic cell depletion modifies FoxP3+ T cell homeostasis and the clinical course of bacterial pneumonia in mice - Lippitsch, Anne; Baal, Nelli; Chukovetskyi, Yuri; Cunningham, Sarah; Michel, Gabriela; Dietert, Kristina; Gurtner, Corinne; Gruber, Achim D.; Bein, Gregor; Hackstein, Holger (Journal of Leukocyte Biology, 2019)
Plasmacytoid dendritic cells (pDC) are critical to antiviral defense because of their high production of type I IFNs; less is known regarding their functions in bacterial infection. Moreover, pDC are involved in immunomodulation. A stable pool of regulatory T cells (Treg) is crucial for maintaining immune homeostasis. However, interactions between pDC and Treg regarding the regulation of Treg homeostasis are understudied. By using BDCA2-DTR mice as a systemic pDC depletion model, we identified increased steady-state numbers of FoxP3+ T cells with an effector Treg-like phenotype in lungs, liver, and spleen tissues. During sublethal, pulmonary Klebsiella pneumoniae infection, pDC deficiency also elevated respiratory FoxP3+ T cell numbers. Additionally, the improvement in acute pneumonia survival until day 5 post infection was accompanied by impaired proinflammatory cytokine production. In contrast, pDC-depleted mice exhibited a delayed clinical recovery during the post-acute phase. Therefore, we assume that pDC act as immunomodulators supporting the rapid onset of immune response in a proinflammatory manner and regulate inflammation or tissue regeneration in the post-acute phase. In summary, pDC assist in FoxP3+ T cell homeostasis and the regulation of Klebsiella-pneumonia progression.
CRIS-Team Scopus Importer:2019-07-16
Keywords: bacterial infection; BDCA2-DTR mice; immunomodulation; inflammation; Klebsiella pneumoniae; regulatory T cells

Rapid generation of monocyte-derived antigen-presenting cells with dendritic cell-like properties - Cunningham, Sarah; Hackstein, Holger (Transfusion, 2021)
Background: One of the major challenges in cellular therapy is the establishment and validation of simple and fast production protocols meeting good manufacturing practice (GMP) requirements. Dendritic cells (DCs) are of particular therapeutic interest, due to their critical role in T cell response initiation and regulation. Conventional wisdom states that DC generation from monocytes is a time-consuming protocol, taking up to 7–9 days. Study Design and Methods: This study systematically screened and validated numerous culture components and conditions to identify the minimal requirements, which can give rise to functional monocyte-derived antigen-presenting cells (MoAPCs) in less than 48 h (36 h MoAPC). A total of 36 h MoAPCs were evaluated in terms of surface marker expression, endocytic capability, and induction of antigen-specific T cell expansion via flow cytometry. Results: Screening of media compositions, glucose concentrations, and surface marker kinetics, particularly DC-SIGN as a DC-specific marker, allowed the generation of DC-like APCs in 36 h (36 h MoAPCs). A total of 36 h MoAPCs displayed a similar phenotype to 48 h MoAPC and standard 7 d MoDCs in terms of HLA-DP,DQ,DR, CD83, and DC-SIGN expression, while CD1a was preferentially expressed in standard MoDCs. Functional evaluation revealed that 36 h MoAPCs displayed reduced endocytosis capabilities and IL-12p70 production. However, 36 h MoAPCs were able to induce T cell expansion both in an allogenic and antigen-specific setting. Conclusion: Our results indicate that mature 36 h MoAPCs possess DC-like capabilities by inducing antigen-specific T cell responses. This study has important implications for the generation of DC-based cellular therapies, allowing a more cost and time-efficient generation of APCs.
CRIS-Team Scopus Importer:2021-04-09
Keywords: 36 h MoAPCs; 48 h MoAPC; antigen-presenting cells; monocytes

Recent Advances in Good Manufacturing Practice-Grade Generation of Dendritic Cells - Cunningham, Sarah; Hackstein, Holger (Transfusion Medicine and Hemotherapy, 2020)
Dendritic cells (DCs) are pivotal regulators of immune responses, specialized in antigen presentation and bridging the gap between the innate and adaptive immune system. Due to these key features, DCs have become a pillar of the continuously growing field of cellular therapies. Here we review recent advances in good manufacturing practice strategies and their individual specificities in relation to DC production for clinical applications. These take into account both small-scale experimental approaches as well as automated systems for patient care.
CRIS-Team Scopus Importer:2020-12-11
Keywords: Dendritic cells; Good manufacturing practice; Monocytes

Scavenging of bacteria or bacterial products by magnetic particles functionalized with a broad-spectrum pathogen recognition receptor motif offers diagnostic and therapeutic applications - Friedrich, Bernhard; Lyer, Stefan; Janko, Christina; Unterweger, Harald; Brox, Regine; Cunningham, Sarah; Dutz, Silvio; Taccardi, Nicola; Bikker, Floris J.; Hurle, Katrin; Sebald, Heidi; Lenz, Malte; et al. (Acta Biomaterialia, 2022)
Sepsis is a dysregulated host response of severe bloodstream infections, and given its frequency of occurrence and high mortality rate, therapeutic improvements are imperative. A reliable biomimetic strategy for the targeting and separation of bacterial pathogens in bloodstream infections involves the use of the broad-spectrum binding motif of human GP-340, a pattern-recognition receptor of the scavenger receptor cysteine rich (SRCR) superfamily that is expressed on epithelial surfaces but not found in blood. Here we show that these peptides, when conjugated to superparamagnetic iron oxide nanoparticles (SPIONs), can separate various bacterial endotoxins and intact microbes (E. coli, S. aureus, P. aeruginosa and S. marcescens) with high efficiency, especially at low and thus clinically relevant concentrations. This is accompanied by a subsequent strong depletion in cytokine release (TNF, IL-6, IL-1β, Il-10 and IFN-γ), which could have a direct therapeutic impact since escalating immune responses complicates severe bloodstream infections and sepsis courses. SPIONs are coated with aminoalkylsilane and capture peptides are orthogonally ligated to this surface. The particles behave fully cyto- and hemocompatible and do not interfere with host structures. Thus, this approach additionally aims to dramatically reduce diagnostic times for patients with suspected bloodstream infections and accelerate targeted antibiotic therapy. Statement of significance: Sepsis is often associated with excessive release of cytokines. This aspect and slow diagnostic procedures are the major therapeutic obstacles. The use of magnetic particles conjugated with small peptides derived from the binding motif of a broad-spectrum mucosal pathogen recognition protein GP-340 provides a highly efficient scavenging platform. These peptides are not found in blood and therefore are not subject to inhibitory mechanisms like in other concepts (mannose binding lectine, aptamers, antibodies). In this work, data are shown on the broad bacterial binding spectrum, highly efficient toxin depletion, which directly reduces the release of cytokines. Host cells are not affected and antibiotics not adsorbed. The particle bound microbes can be recultured without restriction and thus be used directly for diagnostics.
CRIS-Team Scopus Importer:2022-03-11
Keywords: GP-340; Magnetic nanoparticles; Pathogen binding; Sepsis; SRCR domain

SERPINC1 c.1247dupC: a novel SERPINC1 gene mutation associated with familial thrombosis results in a secretion defect and quantitative antithrombin deficiency - Ruf, Maximilian; Cunningham, Sarah; Wandersee, Alexandra; Brox, Regine; Achenbach, Susanne; Strobel, Julian; Hackstein, Holger; Schneider, Sabine (Thrombosis Journal, 2024)
BACKGROUND: Antithrombin (AT) is an important anticoagulant in hemostasis. We describe here the characterization of a novel AT mutation associated with clinically relevant thrombosis. A pair of sisters with confirmed type I AT protein deficiency was genetically analyzed on suspicion of an inherited SERPINC1 mutation. A frameshift mutation, c.1247dupC, was identified and the effect of this mutation was examined on the cellular and molecular level. METHODS: Plasmids for the expression of wild-type (WT) and mutated SERPINC1 coding sequence (CDS) fused to green fluorescent protein (GFP) or hemagglutinin (HA) tag were transfected into HEK293T cells. Subcellular localization and secretion of the respective fusion proteins were analyzed by confocal laser scanning microscopy and Western blot. RESULTS: The c.1247dupC mutation results in a frameshift in the CDS of the SERPINC1 gene and a subsequently altered amino acid sequence (p.Ser417LysfsTer48). This alteration affects the C-terminus of the AT antigen and results in impaired secretion as confirmed by GFP- and HA-tagged mutant AT analyzed in HEK293T cells. CONCLUSION: The p.Ser417LysfsTer48 mutation leads to impaired secretion, thus resulting in a quantitative AT deficiency. This is in line with the type I AT deficiency observed in the patients.
EVALuna2:553194
Keywords: Hereditary antithrombin deficiency; Secretion defect; Frameshift mutation; Thrombosis

The Protein S Erlangen Mutation PROS1c.1904T>C (F635S) Suppresses Secretion. - Reißig, Julian; Cunningham, Sarah; Wandersee, Alexandra; Brox, Regine; Achenbach, Susanne; Strobel, Julian; Hackstein, Holger; Schneider, Sabine (Clinical Laboratory, 2024)
BACKGROUND: The recently identified PROS1 mutation Protein S Erlangen c.1904T>C, resulting in amino acid exchange F635S, is associated with severe quantitative protein S (PS) deficiency and clinical thrombosis. It was hypothesized that this deficiency is due to a secretion defect [1]. This report aims to further elucidate the potential secretion defect of PS Erlangen. METHODS: Coding sequences (CDS) of wild type (WT) PROS1 (encoding PS) and mutated PROS1c.1904T>C (encoding PSF635S) were cloned in front of the CDS of green fluorescent protein (GFP), and the respective plasmids were introduced into HEK293T cells. PROS1-GFP and PROS1c.1904T>C-GFP expressing HEK293T cell lines were analyzed by confocal laser scanning microscopy and western blot for cellular proteins and proteins secreted to the growth medium. RESULTS: Western blot analysis revealed a significantly reduced secretion of PSF635S compared to WT PS. This observation was confirmed by the detection of mutant PSF635S-GFP fusion exclusively in the endoplasmic reticulum (ER), while PS-GFP passed through the entire secretory pathway, as indicated by the localization within both the ER and Golgi apparatus. CONCLUSIONS: The Protein S Erlangen mutation results in type I PS deficiency caused by a secretion defect.
EVALuna2:562075
Keywords: point mutation; PROS1; secretion pathway; Protein S deficiency; secretion defect

Thrombocyte apheresis cassettes as a novel source of viable peripheral blood mononuclear cells - Cunningham, Sarah; Buchele, Vera; Brox, Regine; Strasser, Erwin; Hackstein, Holger (Transfusion, 2020)
BACKGROUND: Traditionally, white blood cells (WBCs) are collected from buffy coats or freshly drawn blood. However, the increasing demand for peripheral blood mononuclear cells (PBMCs) in the research phases of immunological therapy development makes it necessary to identify alternative sources of these cells. STUDY DESIGN AND METHODS: Leukapheresis products are cost intensive and not offered by all blood banks. Therefore, thrombocyte apheresis cassettes (TACs), plateletpheresis waste products, were investigated as a possible low-cost and easily accessible blood source for research laboratories. The recovery rate, phenotype, and functionality of WBC subsets from TAC are unknown and were investigated in comparison to frequently used blood resources via flow cytometry. RESULTS: On average, TACs provide 30.3 × 106/mL PBMCs, situating themselves between peripheral whole blood (WB; 5.35 × 106/mL) and leukoreduction system chamber (LRSC; 163.9 × 106/mL) yields. Frequencies of CD14, CD3, CD4, CD8, CD56, CD19, and CD11c positive cells in TACs correlate with normal proportions of WBC populations. Stimulation of TAC-derived PBMCs by lipopolysaccharide (LPS) and resiquimod (R848) showed no significant differences in expression levels of human leukocyte antigen (HLA)-DR, DQ, DP, and CD86 or cytokine secretion compared to other blood source derived PBMC. Following stimulation with LPS or R848, comparable levels of tumor necrosis factor-α, interleukin-10, and interleukin-1β could be measured between TAC, LRSC, and WB. Additionally, TAC-derived T cells retained their proliferation capability and were able to produce interferon-γ following T-cell receptor stimulation. CONCLUSION: TACs provide a cost-effective source of viable and functional human blood cells that can readily be used for clinical and laboratory investigations after plateletpheresis preparation.
CRIS-Team Scopus Importer:2020-03-27

TNF promotes DECTIN2 family C-type lectin receptor expression in human macrophages. - Haberkamp, Carl; Allabauer, Ida; Blaha, Niklas; Bodendorfer, Barbara; Cunningham, Sarah; Hörning, André; Lang, Roland (Journal of Leukocyte Biology, 2023)
TNF blockade constitutes an effective therapy for inflammatory bowel disease, yet increases the risk for infection, including active tuberculosis. The DECTIN2 family C-type lectin receptors MINCLE, MCL, and DECTIN2 sense mycobacterial ligands and activate myeloid cells. In mice, upregulation of DECTIN2 family C-type lectin receptor after stimulation with Mycobacterium bovis Bacille Calmette-Guérin requires TNF. Here, we investigated whether TNF controls inducible C-type lectin receptor expression in human myeloid cells. Monocyte-derived macrophages were stimulated with Bacille Calmette-Guérin and the TLR4 ligand lipopolysaccharide, and expression of C-type lectin receptor was analyzed. Bacille Calmette-Guérin and lipopolysaccharide strongly upregulated messenger RNA expression of DECTIN2 family C-type lectin receptor but not of DECTIN1. Bacille Calmette-Guérin and lipopolysaccharide also induced robust production of TNF. Recombinant TNF was sufficient to upregulate expression of DECTIN2 family C-type lectin receptor. Blocking TNF with the TNFR2-Fc fusion protein etanercept abrogated, as expected, the effect of recombinant TNF and impaired induction of DECTIN2 family C-type lectin receptor by Bacille Calmette-Guérin and lipopolysaccharide. Flow cytometry confirmed upregulation of MCL at the protein level by recombinant TNF and showed inhibition of Bacille Calmette-Guérin-induced MCL by etanercept. To investigate the impact of TNF on C-type lectin receptor expression in vivo, we analyzed peripheral blood mononuclear cells of patients with inflammatory bowel disease and observed downregulation of MINCLE and MCL expression after therapeutic TNF blockade. Together, TNF is sufficient to upregulate DECTIN2 family C-type lectin receptor in human myeloid cells and contributes to this process after encounter with Bacille Calmette-Guérin or lipopolysaccharide. Impaired C-type lectin receptor expression in patients receiving TNF blockade may dampen the sensing of microbes and defense against infection.
EVALuna2:531674
Keywords: MINCLE; MCL; DECTIN2; TNF blockade; mycobacteria; inflammatory bowel disease

Validation of a SARS-CoV-2 RNA RT-PCR assay for high-throughput testing in blood of COVID-19 convalescent plasma donors and patients - Strasser, Erwin; Steininger, Philipp; Korn, Klaus; Achenbach, Susanne; Tenbusch, Matthias; Cunningham, Sarah; Zimmermann, Robert; Überla, Klaus; Hackstein, Holger (Transfusion, 2020)
Background The frequency of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) RNAemia in blood donors is uncertain. Thus, assays for SARS-CoV-2 RNA detection in blood, validated on commercially available polymerase chain reaction (PCR) systems, are required to allow a good comparability of data.
CRIS-Team WoS Importer:2020-11-27